The Impact of Assessment in Jigsaw Cooperative Learning Method and Logical Thinking Ability on Biology Achievement by Controlling Students’ Prior Knowledge - Puger, I Gusti Ngurah (Thinking Skills and Creativity Journal, 2023)
Biology teachers, particularly junior high teachers should be able to select appropriate teaching methods thus teaching materials that are communicated can be understood concretely and formally. This study aims to analyze the effect of assessment using jigsaw cooperative learning method and logical thinking ability on Biology achievement after controlling students’ prior knowledge. This study was conducted with design treatment by level 2 x 2. Through random sampling, it was decided 84 students as sample. All of requisite testing from two-way Ancova was fulfilled. The result of data analyzed with two-way Ancova, after controlling students’ prior knowledge showed that the students achievement in biology who took performance assessment was better than the students who took written assessments in cooperative learning method using jigsaw type; there was an interaction effect between assessment in cooperative learning method of jigsaw type and logical thinking ability toward the students achievement in biology; for those students who had high logical thinking ability were more compatible to take part in performance assessment in cooperative learning method using jigsaw type; and for the group of students who had lower logical thinking ability were more compatible to take written assessment in cooperative learning method of jigsaw type. Based on the conclusion of this study, it is suggested to biology teachers that the type of assessment applied in learning method, logical thinking, biology learning outcomes, and students’ prior knowledge should be taken into consideration in conducting learning process.